Das raias ao museu: um estudo de caso sobre o processo de documentação museológica da coleção de medalhas da atleta paraense Suzete Montalvão - MARTINS, Gabriele de Oliveira (2019)
The present work aims to investigate the relationship between museum-sport-woman through a museological perspective, which questions the (in) visibility of women athletes both in sport and in museums themselves, besides highlighting that this sport theme is not yet treated in the museums of the metropolitan region. Thus, it brings to light the history of Athletics from a broader survey, internationally, to the contextualization of the sport in Pará and especially the former athlete Suzete Montalvão and the construction of the Museu Itinerante do Atletismo Paraense. To this end, the main focus was to highlight the importance of the museological documentation of the medals for the systematization, retrieval and safeguarding of information through objects, making use of a private collection, the Collection of Medals of former Pará athlete Suzete Montalvão in order to realize that it can contribute to the reconstitution of stories, identities and memories of the groups that identify with the modality. Thus, we sought to reflect the concepts related to Museum and Museology within the scope of the study object typology and the environment in which it is inserted. For this, an exploratory methodology was used with questionnaires, interviews, bibliographical research and object analysis through the application of documentary instruments designed to contribute to this study. Thus, in order to relate the material heritage, its preservation and the safeguarding of the sporting memory of Pará athletics, besides considering the space and the existing collections of female athletes with the purpose of also emphasizing the gender study in the classroom and therefore, to encourage students to think about the presence / absence of women in certain places, this paper aimed to analyze the relationship between sport with the museum and the museum spaces through the museological documentation, which seeks to emphasize the importance of intrinsic and extrinsic information acquisition that can help to understand data for further research on the elements that make up the object and its environment, such as the possibility of relating political, economic, social and cultural themes.